The Kynurenine Pathway of Tryptophan Catabolism, CD4+ T-Cell Recovery, and Mortality Among HIV-Infected Ugandans Initiating Antiretroviral Therapy - Byakwaga, Helen; Boum II, Yap; Huang, Yong; Muzoora, Conrad; Kembabazi, Annet; Weiser, Sheri D; Bennett, John; Cao, Huyen; Haberer, Jessica E; Deeks, Steven G; Bangsberg, David R; McCune, Joseph M.; et al. (Oxford University Press, 2014)
Background. Human immunodeficiency virus (HIV) infection–induced indoleamine 2,3-dioxygenase-1 (IDO) expression in activated monocytes and dendritic cells catabolizes tryptophan to kynurenine and other downstream catabolites that inhibit T-cell proliferation and interleukin 17 (IL-17) production. The prognostic significance of this pathway in treated HIV disease is unknown. Methods. We measured systemic IDO activity (calculated as the ratio of plasma levels of kynurenine to tryptophan; hereafter, the “KT ratio”) in HIV-infected Ugandans before and during antiretroviral therapy (ART)–mediated viral suppression and its association with the rate of subsequent CD4+ T-cell count recovery and mortality. Results. Among 435 participants, a higher pre-ART KT ratio was associated with a higher plasma virus load (P < .001) and lipopolysaccharide level (P = .018), a lower CD4+ T-cell count (P < .001), and female sex (P = .047). Through month 12 of ART-mediated viral suppression, the plasma KT ratio decreased by approximately 50% (P < .001). After adjustment for pre-ART CD4+ T-cell count, virus load, age, and sex, a higher month 12 KT ratio predicted a slower rate of subsequent CD4+ T-cell count recovery (P = .001). Thirty-nine participants died. After adjustment for pre-ART CD4+ T-cell count, virus load, body mass index, sex, and age, a higher pre-ART and month 6 KT ratio predicted increased mortality (P ≤ .016). Conclusions. The kynurenine pathway of tryptophan catabolism independently predicts poor CD4+ T-cell count recovery and increased mortality among HIV-infected Ugandans initiating ART and may be an important target for interventions.
Keywords: Tryptophan; kynurenine; indoleamine 2,3-dioxygenase-1; HIV; mortality; antiretroviral therapy; Uganda